Pemberian Ganti Rugi Lahan Masyarakat dalam Pengelolaan Tambang di Kabupaten Kolaka - Agusmawati, Mega; Jabalnur, Jabalnur; Hasima, Rahman (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
This research aims to find out the legal consequences of the provision of land compensation by the company PT. Ceria Nugraha Indotama (PT. CNI) to the community that is not in accordance with the agreement and to find out the form of legal remedies carried out by the people of Wollo Village, Wollo District, Kolaka Regency against the provision of land compensation to the community that is not in accordance with the agreement. The research method used is Empirical research. The results of this study show that, (1) The legal consequences of the provision of land compensation by the company PT. Ceria Nugraha Indotama (PT. CNI) to the community that is not in accordance with the agreement is an act of default against the community holding land rights in Wollo Village, Wollo District, Kolaka Regency, because the company does not fulfill its obligations in the agreement made orally with the community regarding the nominal amount of compensation for land acquisition, so as to cause material and immaterial losses and (2) legal remedies that can be carried out by the Village community Wolo, Wollo District, Kolaka Regency against the provision of land compensation to the community that is not in accordance with the non-litigation route, namely the negotiation method with a mechanism as stipulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.